Rancang Bangun Alat Fiksasi Pemeriksaan Radiografi Thorax Proyeksi Antero Posterior (AP) pada Balita - Ira Sandi Tunny; Maritje S. J Malisngorar; Rini Hatma Rusli; Iksan Soumena; Bambang Ariyanto (Lembaga Pengembangan Kinerja Dosen, 2023)
This fixation tool made aiming to reduce the movement of the patient toddler at the time of the thorax projection radiographs Antero Posterior supine and parents or relatives of patients do not need to hold patients toddler at the time of examination that is not exposed to X-ray radiation. This study used an experimental method, which aims to create a fixation device in the AP projection thoracic radiographs supine in infants that can support the process of examination of the thorax radiography in young children, so as to provide optimal results radiographs. While the data collection methods used were observation, interviews and questionnaires which aims to determine the effectiveness of fixation devices that have made the author. Based on observations, interviews and questionnaires conducted by the author, showed that the use of fixation devices have been quite effective in supporting the process of projection thoracic radiographs AP supine in infants and can produce optimal radiograph thorax